A revision of the mycoheterotrophic genus Epirixanthes (Polygalaceae) in Vietnam - Nuraliev, Maxim S.; Lyskov, Dmitry F.; Averyanov, Leonid V.; Le, Tuan Anh; Kopylov-Guskov, Yury O.; Sennikov, Alexander N.; Dac, Le Xuan; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Yudina, Sophia V. (Phytotaxa, 2026)
A taxonomic revision of Epirixanthes, the only mycoheterotrophic genus of Polygalaceae, is presented for Vietnam. Two species are recognized, of which E. elongata is known to be widely distributed across tropical Asia and E. kinabaluensis was considered endemic to Malesia prior to our study. Several nomenclatural inconsistencies are resolved for the names related to Epirixanthes. The original spelling of the generic name is confirmed as nomenclaturally correct because of being derived from conventional phonetic variants in Medieval Latin. Morphological descriptions of both Vietnamese species are significantly amended, reflecting novel data on the gross structure of their flowers and on intraspecific variation. For each species, the distinction from its most similar congener is summarized. Extensive illustrations of inflorescences and flowers of both species are provided; the inner structure of the intact flowers is illustrated with 3D images produced using X-ray microtomography.